Fat talk : what girls and their parents say about dieting - Nichter, Mimi (Harvard University Press, 2000)
Surveys show that half of American teen-aged girls are dieting and many are at risk from eating disorders. This text examines differences between the black and white subjects interviewed and the issues that mothers face in raising healthy daughters.